Optical analysis of glioma: fourier-transform infrared spectroscopy reveals the IDH1 mutation status - Uckermann, Ortrud; Juratli, Tareq A.; Galli, Roberta; Conde, Marina; Wiedemuth, Ralf; Krex, Dietmar; Geiger, Kathrin; Temme, Achim; Schmitz-Schackert, Gabriele; Koch, Edmund; Steiner, Gerald; Kirsch, Matthias (Clinical cancer research, 2018)
Purpose: Somatic mutations in the human cytosolic isocitrate dehydrogenase 1 (IDH1) gene cause profound changes in cell metabolism and are a common feature of gliomas with unprecedented predictive and prognostic impact. Fourier-transform infrared (FT-IR) spectroscopy addresses the molecular composition of cells and tissue and was investigated to deduct the IDH1 mutation status. - Experimental Design: We tested the technique on human cell lines that were transduced with wild-type IDH1 or mutated IDH1 and on 34 human glioma samples. IR spectra were acquired at 256 positions from cell pellets or tissue cryosections. Moreover, IR spectra were obtained from fresh, unprocessed biopsies of 64 patients with glioma. - Results: IDH1 mutation was linked to changes in spectral bands assigned to molecular groups of lipids and proteins in cell lines and human glioma. The spectra of cryosections of brain tumor samples showed high interpatient variability, for example, bands related to calcifications at 1113 cm−1. However, supervised classification recognized relevant spectral regions at 1103, 1362, 1441, 1485, and 1553 cm−1 and assigned 88% of the tumor samples to the correct group. Similar spectral positions allowed the classification of spectra of fresh biopsies with an accuracy of 86%. - Conclusions: Here, we show that vibrational spectroscopy reveals the IDH1 genotype of glioma. Because it can provide information in seconds, an implementation into the intraoperative workflow might allow simple and rapid online diagnosis of the IDH1 genotype. The intraoperative confirmation of IDH1 mutation status might guide the decision to pursue definitive neurosurgical resection and guide future in situ therapies of infiltrative gliomas. Clin Cancer Res; 24(11); 2530-8. ©2017 AACR. - See related commentary by Hollon and Orringer, p. 2467
Published online: December 19, 2017
Gesehen am 19.08.2019